Odpowiedzi

2009-11-27T20:38:49+01:00
A) x³-6x²+11x-6=0
W(1)=1-6+11-6=12-12=0
dzielimy przez (x-1)
x³-6x²+11x-6:(x-1)=x²-5x+6czyli
x³-6x²+11x-6=(x-1)*(x²-5x+6)
wyznaczam pierwiastki r-nia x²-5x+6
Δ=25-24=1
√Δ=1
x1=5-1/2=2
x2=5+1/2=3
zatem
(x-1)(x-2)(x-3)=0 czyli x=1 , x=2 ,x=3

b) x³+7x²-x-7=0
x²(x+7)-(x+7)=0
(x+7)(x²-1)=0
(x+7)(x-1)(x+1)=0
x=7 , x=1 , x=-1
c) -3x³+2x²+9x-6=0
-3x(x²-3)+2(x²-3)=0
(x²-3)(2-3x)=0
(x-√3)(x+√3)(2-3x)=0
x=√3 , x=-√3, x=2/3
d) x³+5x²=x+5
x³+5x²-x-5=0
x²(x+5)-(x+5)=0
(x+5)(x²-1)=0
(x+5)(x-1)(x+1)=0
x=-5 ,x=1 ,x=-1
e) (x²+4)(x²-4)=0
(x²+4)(x-2)(x+2)=0
x=2 i x=-2
f) x³-7x+6>0
W(1)=1-7+6=0
dzielimy
x³-7x+6:(x-1)=x²+x-6
czyli
(x-1)(x²+x-6)>0
Δ=1+24=25,√Δ=5
x1=-1-5/2=-3
x2=-1+5/2=2
(x-1)(x+3)(x-2)>0
x∈(-∞,-3) i (1,2)
g) (x²-3)²-4≤0
x⁴-6x²+9-4≤0
x⁴-6x²+5≤0
t=x², t>0
t²-6t+5≤0
Δ=36-20=16
√Δ=4
t1=6-4/2=1
t2=6+4/2=5, czyli
x²=1 stąd x=-1 i x=1
x²=5 czyli x=+-√5
1 5 1